2005
DOI: 10.1007/s00428-005-1214-6
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of NOTCH1 and ABL1 gene loci is a frequent aberration in enteropathy-type T-cell lymphoma

Abstract: We have shown previously that amplification of chromosomal region 9q34 is the most frequent aberration in enteropathy-type T-cell lymphoma (ETL). To determine the minimum amplified 9q34 region and identify possible candidate gene(s), we performed a detailed microsatellite screening and quantitative real-time PCR (QPCR) on 26 ETL cases. Microsatellite analysis revealed allelic imbalance in both ABL1 and NOTCH1 gene loci (microsatellites D9S290-D9S1847 and D9S158 flanking the former and latter genes, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 33 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…NEK6 is a never in mitosis a-related kinase 6 and is required for progression of the cell cycle through mitosis [20]. A microsatellite screening and quantitative real-time polymerase chain reaction study conducted in Europe showed that the NOTCH1 gene of chromosome 9q34.3 is frequently amplified in EATL and suggested that NOTCH1 is the primary target of genomic DNA amplification in chromosome 9q34 [21]. In type 2 EATL, a gain in 1q and 5q is rare; and a gain of the c-Myc oncogene is common [4].…”
Section: Discussionmentioning
confidence: 99%
“…NEK6 is a never in mitosis a-related kinase 6 and is required for progression of the cell cycle through mitosis [20]. A microsatellite screening and quantitative real-time polymerase chain reaction study conducted in Europe showed that the NOTCH1 gene of chromosome 9q34.3 is frequently amplified in EATL and suggested that NOTCH1 is the primary target of genomic DNA amplification in chromosome 9q34 [21]. In type 2 EATL, a gain in 1q and 5q is rare; and a gain of the c-Myc oncogene is common [4].…”
Section: Discussionmentioning
confidence: 99%
“…NOTCH1 or NEK6 have been proposed as genes possibly affected by the 9q gains. (78,80) The prognosis of both subtypes of EATL is very poor with conventional chemotherapy, also due to local complications and the underlying poor nutritional and immunological conditions (Table 3, Data S1).…”
Section: Extranodal Lymphomasmentioning
confidence: 99%
“…The newly characterized HMGN variant, HMGN5, has not yet been implicated in any published phenotypes. Targets of potential biological interest include the members of the Lce3 family, which are involved in the etiology of autoimmune disease (62); the mitogens Eapp and Abl1 (63,64), which are upregulated in Hmgn5 tm1/tm1 liver; and centrosomal protein Cep57, which is down-regulated in the Hmgn5 tm1/tm1 spleen, and this suggests that HMGN5 mutant cells might be prone to aneuploidy (65).…”
Section: Hmgn Variants Fine Tune the Fidelity Of The Cellular Transcrmentioning
confidence: 99%